“KONTAMINASI LOGAM BERAT DI KOLOM AIR, SEDIMEN DAN DAGING IKAN NGONGAI (Bagarius bagarius) DI KAWASAN KONSERVASI BATANG KUANTAN SIJUNJUNG” - Masykury, Rizka; Syandri, Hafrijal; Azrita, Azrita (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2023)
This study aims to analyze the content of heavy metals in the water column, sediment, and meat of Bagarius bagarius fish living in the Batang Kuantan River conservation area. The heavy metals analyzed included Hg, Pb, Cu, Zn, and Cd. The research was conducted between April and May 2022 at three stations in the Batang Kuantan Sijunjung Conservation area. Sample analysis was performed at the West Sumatra Provincial Health UPTD Laboratory. The concentration of heavy metals in the water column, sediment, and fish meat was determined using a spectrophotometer based on the AAS method. The results indicated that Hg (0.015 mg/L) had the highest content in the water column at station 3. In sediment, Zn (30.92 mg/L) showed the highest concentration at station 1, whereas, in fish meat, Pb (15.51 mg/kg) was the highest at station 3. The concentration of Hg in the water column exceeded the quality standard for River Water Quality Standards and the Like Class III, as specified in Appendix VI of Government Regulation of the Republic of Indonesia No. 22 of 2021 regarding the Implementation of Environmental Protection and Management, which is 0.002 mg/L. Additionally, the concentration of Cd at station 3 was 3,199 mg/kg, surpassing the sediment quality standard set by the Australian and New Zealand Environment and Conservation Council (ANZECC, 2000) of 1.5 mg/kg. The highest concentration of Pb in fish meat was observed at station 3, which exceeded the quality standard for heavy metal Pb in fish meat and processed products according to SNI Number 7387 of 2009, which sets the maximum limit of heavy metal contamination in food at 0.3 mg/kg.